An Explanation for the Role of the Amygdala in Aesthetic Judgments - Jacobs, Richard H. A. H.; Cornelissen, Frans W. (Frontiers in Human Neuroscience, 2017)
It has been proposed that the top-down guidance of feature-based attention is the basis for the involvement of the amygdala in various tasks requiring emotional decision-making (Jacobs, Renken, Aleman & Cornelissen, 2012). Aesthetic judgements are correlated with particular visual features and can be considered emotional in nature (Jacobs et al., 2016). Moreover, we have previously shown that various aesthetic judgements result in observers preferentially attending to different visual features (Jacobs et al., 2010). Here, we argue that – together – this explains why the amygdalae become active during aesthetic judgements of visual materials. We discuss potential implications and predictions of this theory that can be tested experimentally.